If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 22m = 28x + 15m Reorder the terms: 22m + 14x = 28x + 15m Reorder the terms: 22m + 14x = 15m + 28x Solving 22m + 14x = 15m + 28x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-15m' to each side of the equation. 22m + -15m + 14x = 15m + -15m + 28x Combine like terms: 22m + -15m = 7m 7m + 14x = 15m + -15m + 28x Combine like terms: 15m + -15m = 0 7m + 14x = 0 + 28x 7m + 14x = 28x Add '-14x' to each side of the equation. 7m + 14x + -14x = 28x + -14x Combine like terms: 14x + -14x = 0 7m + 0 = 28x + -14x 7m = 28x + -14x Combine like terms: 28x + -14x = 14x 7m = 14x Divide each side by '7'. m = 2x Simplifying m = 2x
| 7x+9=-24-4x | | -3x^2+14x-9=0 | | 3x+6h=9x+3h | | R+7.2=8.1 | | 3x+6=9x+3 | | x^2/3-4/25=0 | | 26-8x=14+4x | | -2.68=x-1.9-1.3x | | -3(2x+3)=12 | | 6+x=44 | | 4[6-1(1+2m)]+10m=2(10-3m)+8m | | x^3+bx^2+cx+d=0 | | 6(3+6x)-2=88 | | 7x+8=5x | | -0.9n-1.49n=2.151 | | 2x+12=2y-1 | | b^2+7b+6=-6 | | xy3/x | | -0.9-1.49n=2.151 | | 2(2x+1)=17 | | y^2/3-25/64=0 | | 2.1(6x/3-4.7)=8.66 | | 3a^2=-16+16a | | 11m+4(m-3)+6m=4m-12 | | [y+2]=3 | | 2/300 | | 6x^2-21x-18= | | 0=(x-2)(x-i)(x+i)(x-1-i)(x+1+i) | | f(x)=(x-2)(x-i)(x+i)(x-1-i)(x+1+i) | | 2.1(6x/3-4.7)=20 | | 192/6 | | 2(-1-3)(-1-3)(-1-3)-5= |